ANALISIS KELAYAKAN USAHATANI TANAMAN JERUK DI DESA KARANGCENGIS, KECAMATAN BUKATEJA, KABUPATEN PURBALINGGA - Lili Akhwandi; Dumasari Dumasari; Pujiharto Pujiharto (Universitas Muhammadiyah Purwokerto, 2016)
The condition of citrus farming in karangcengis village, Bukateja subdistrict, Purbalingga regency was the background of this study. it was to know wheter this farming was feasible to run or not.The study was aimed at knowing the cust of productions, income, yield per harvesttime. The method was survey method.The samples were taken by purposive sampling. To know about the farmes’ income, the data were analyezed by reducing the admission with the total cost. R/C was used to know every harvest time and (NPV, IRR, Net B/C ratio) are usedto know wheter the farming was feasible to run or not.The result showed that the average production for each harvest time in 2014 was 2.242,16 kg, in 2015 the average production was 3.3063,71 kg and in 2016 the average production was 1.693,43 kg. The farmes incomein 2014 was Rp.5.570.130,96 with land width of 0,25 Ha and the number of plants was 175 Citurs Plants. The farmes income in 2015 was Rp 9.337.031,3 with the land widht of 0,25 Ha and the numbers of plants was 175 citrus plants.The farmes incomen in 2016 wasRp.4.564.079,9 with the land width of 0,25 Ha and the number of plants 175 citrus plants in 2014, R/C value was 2,3 in 2015, R/C value was 3,1. In 2016, R/C value was 2,5 NPV value that was obtaint during three harvest times was 14.204.241.IRR value that was obtainedduring three harvest times was 28,20%. Net B/C ratio that Wass obtained during three harvest times was 2,519. Therefore, it can be summed up that the citrus farming in Karangcengis village Bukateja subdistrict Purbalingga regency is feasible to run